2018
DOI: 10.1016/j.jmps.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous yield behavior of fused silica glass

Abstract: We develop a critical-state model of fused silica plasticity on the basis of data mined from molecular dynamics (MD) calculations. The MD data is suggestive of an irreversible densification transition in volumetric compression resulting in permanent, or plastic, densification upon unloading. The MD data also reveals an evolution towards a critical state of constant volume under pressure-shear deformation. The trend towards constant volume is from above, when the glass is overconsolidated, or from below, when i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
(129 reference statements)
1
8
0
Order By: Relevance
“…These alkali‐rich regions tend to densify preferentially under pressure, 26 but the densification of these regions does not affect the number of constraints (rigidity) in the sample 38 . For Boro33, its minimum in modulus is in agreement with the elastic moduli anomaly found in silica 39‐41 and also silicate glasses 26 . It has been shown that the critical composition at which the transition between anomalous and normal behavior happens is located at 15% Na 2 O 42 and the anomalous behavior mainly results from the isotropic collapse of glass's network due to more free volume in the structure 23,26 rather than the coordination change 40 This anomaly is thus not observed in N‐BK7 because of more alkali amount.…”
Section: Discussionsupporting
confidence: 73%
“…These alkali‐rich regions tend to densify preferentially under pressure, 26 but the densification of these regions does not affect the number of constraints (rigidity) in the sample 38 . For Boro33, its minimum in modulus is in agreement with the elastic moduli anomaly found in silica 39‐41 and also silicate glasses 26 . It has been shown that the critical composition at which the transition between anomalous and normal behavior happens is located at 15% Na 2 O 42 and the anomalous behavior mainly results from the isotropic collapse of glass's network due to more free volume in the structure 23,26 rather than the coordination change 40 This anomaly is thus not observed in N‐BK7 because of more alkali amount.…”
Section: Discussionsupporting
confidence: 73%
“…Nowadays, molecular dynamics (MD) simulations have been widely used to study structures and dynamic response of silica glass. [17][18][19][20][21][22][23][24][25][26] Zeidler et al [17] used MD and experiments to establish the relationship between the ring size and Si-O coordination number of silica glass under cold compression conditions, which is helpful for understanding the densification process. Huang et al [18] simulated the cold and hot compression of silica glass.…”
Section: Introductionmentioning
confidence: 99%
“…1a, resulting in a strongly non-convex elastic domain in the pressure-shear stress plane. Several authors [MR08,SHCO18] have performed molecular dynamics calculations of amorphous solids deforming in pressure-shear and have found that the resulting deformation field forms distinctive patterns to accommodate permanent macroscopic deformations, Fig. 1b.…”
Section: Introductionmentioning
confidence: 99%